Electrodeposition of aluminium film on P90 Li-Al alloy as protective coating against corrosion - Bardi, U.; Caporali, S.; Craig, M.; Giorgetti, A.; Perissi, I.; Nicholls, John R. (Elsevier Science B.V., Amsterdam., 2009)
In this paper we report on the electrodeposition of thin aluminium layers on P90 lithium–aluminium alloy at room temperature from a chloroaluminate ionic liquid (1-butyl-3-methyl imidazolium heptachloroaluminate [BMIm]Al2Cl7). We found that the treatment of the P90 sample's surface is a key point to obtain good quality coatings. On freshly mechanically polished surfaces, thin (about 24 µm), homogeneous and dense aluminium layers were obtained at 10 µm h− 1 deposition rate. Finally, the corrosion resistance of the uncoated and Al-coated samples was investigated by means of electrochemical techniques such as open-circuit voltage curves, impedance spectroscopy and potentiodynamic polarization in 3.5 wt.% NaCl aqueous solution. We found that the protective aluminium layer significantly reduces the corrosion rates of the P90 Li–A
Keywords: Ionic liquids; Electrodeposition; Lithium-aluminium alloy; Corrosion; XPS